Synthesis, Characterization and Biological Evaluation of Some Novel Regioisomers of Ropivacaine Analogues: An Anaesthetic Drug - Sharavanan, S.P.N.; Venkatesan, C.S.; Bhaskara Suresh Raju, D.; Kabilan, S. (Asian Journal of Chemistry, 2020)
A series of ropivacaine analogues were synthesized by altering the methyl group substituent in the aromatic ring. The synthesized compounds (2a-f and 3a-f) were characterized by using IR, NMR and HRMS analysis and then compounds 3a-3f were screened in vitro anticancer (MTT assay) activity against breast cancer cell line (MCF-7), antibacterial and antioxidant (DPPH scavenging assay) studies. The biological studies revealed that the compounds 3c and 3f have shown a good inhibitory activity against MCF-7 cell line. Compounds 3e, 3b, 3c and 3f showed moderate antioxidant activity. There was no inhibition observed against both Gram-positive and Gram-negative bacteria.